ISPC Commentary on the Proposal for CRP6 - March 2011 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2011)
ISPC Commentary on the proposal for CRP 6: Forests Trees and Agroforestry: Livelihoods, Landscapes and Governance (Version of February 2011).